The Influence of Learning Styles on Students' Scientific Attitudes in Science Learning at SDN 06 Kendari - L. Parisu, Chairan Zibar; Sisi, La; Juwairiyah, Arna (International Journal of Management and Education in Human Development, 2025)
This study aims to analyze the influence of learning styles on students' scientific attitudes in science learning at SDN 06 Kendari. Learning styles are an important factor that can influence how students understand science concepts and develop scientific attitudes such as curiosity, objectivity, openness, and honesty in the process of acquiring knowledge. The research method used is ex-post. A post facto study with a quantitative approach. The research population was all 60 fifth-grade students of SDN 06 Kendari, with a research sample of 30 people selected using the simple random sampling technique. Random sampling. The research instrument was a learning style questionnaire compiled based on visual, auditory , and kinesthetic categories , as well as a scientific attitude questionnaire developed based on scientific attitude indicators according to the elementary school science curriculum. Data were analyzed using simple linear regression. The results showed that there was a significant influence of learning style on students' scientific attitudes (p < 0.05). Students with a visual learning style tended to show scientific attitudes in the aspects of order and accuracy, while auditory students were superior in the aspect of openness to ideas, and kinesthetic students stood out in curiosity and exploratory activities. These findings emphasize the importance of teachers understanding students' learning styles in designing varied science learning so that they can foster optimal scientific attitudes. Thus, adjusting teaching methods based on students' learning styles is an important strategy in improving the quality of science learning in elementary schools.